Ultrasonic spot-welding of AA 6061-T6 aluminium alloy: Optimization of process parameters, microstructural characteristics and mechanical properties of spot joints - P. Rajalingam; S. Rajakumar; S. Kavitha; Tushar Sonar (International Journal of Lightweight Materials and Manufacture, 2024)
The ultrasonic spot welding (USW) is used to develop the lap joints of AA 6061-T6 aluminium alloy because it is difficult to spot weld using resistance spot welding (RSW) and laser beam spot welding (LBSW) processes due to its high electrical conductivity, thermal conductivity and light reflectivity respectively. The main objective of this investigation is to optimize the USW parameters specifically welding time (s), amplitude (%) and pressure (bar) for enhancing the tensile shear fracture load (TSFL) bearing capability of AA 6061-T6 aluminium alloy lap joints for automotive applications. The statistical response surface methodology (RSM) was utilized for generating strength prediction models (SPM) and validated using analysis of variance (ANOVA). The RSM is widely used for optimizing the process parameters as it provides greater information such as optimum conditions, direct effect of process parameters and performance prediction from limited number of experiments compared to other optimization techniques. The response surfaces were created using RSM and analyzed. The effect of USW parameters on macrostructure, microstructure and TSFL of USW joints was studied. From the results, it was observed that the USW joints created using the welding amplitude of 100%, welding time of 21 s and welding pressure of 6 bar exhibited greater TSFL capacity of 5.08 kN. The SPM accurately predicted the TSFL of USW joints within 5% error on 95% confidence. Welding pressure disclosed major effect on TSFL of USW joints followed by welding amplitude and time. The greater TSFL of USW joints is imputed to the better coalescence of weld surfaces and refined microstructure.